Meal satisfaction analysis of patients at RSUD dr. H. Abdul Moeloek Lampung province - Usdeka Muliani; Andi Eka Yunianto; Sutrio (ARGIPA (Arsip Gizi dan Pangan), 2022)
Patient eating satisfaction is an indicator of the success of organizing food in the hospital. One way to evaluate the success of organizing a patient's meal is from the remaining food. Currently, there are many hospitals with leftover food from patients that exceed the established standards. The aim of the study was to analyze the food satisfaction of inpatients with leftovers at hospital of dr. H. Abdul Moeloek, Lampung Province. This type of analytic observational research with a cross sectional design. The number of samples in this study were 66 people. The chi-square test was used to analyze the relationship between patient satisfaction and food waste. There is a relationship between taste (p=0.000), time of distribution (p=0.028), and the appearance of the waitress (p=0.028) and food waste, and there is no relationship between the completeness of cutlery and food waste (p=0.095). This study shows that there is a significant relationship between the taste, time of distribution, and the appearance of the waiter with leftovers, but not the completeness of cutlery. It is recommended that the Nutrition Installation of dr. H. Abdul Meoloek Hospital conduct an evaluation to improve the taste of food, the right time of distribution, the appearance of better waiters.